1997
DOI: 10.1074/jbc.272.17.11026
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Epidermal Growth Factor Receptors by Nerve Growth Factor in PC12 Cells Is p140 -, Ras-, and Src-dependent

Abstract: PC12 cells, derived from a rat pheochromocytoma, have been extensively used as a model of neuronal differentiation (1), because the cells acquire the phenotype of sympathetic neurons and stop dividing in response to nerve growth factor (NGF) 1 (2).In PC12 cells, NGF interacts with two distinct plasma membrane receptor proteins: p75 NGFR , a cysteine-rich glycoprotein having a relatively low affinity for NGF (3), and p140 trk , a receptor tyrosine kinase activated by NGF, which binds NGF with high affinity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…One way in which the neurotrophins promote cellular differentiation may be to interfere with mitogenic signals. Indeed, previous data from this laboratory suggest that one action of NGF on PC12 cells is the long term down-regulation of mitogen receptors (9,10). The present experiments demonstrate that NGF also has profound and immediate effects on mitogen signaling.…”
supporting
confidence: 57%
“…One way in which the neurotrophins promote cellular differentiation may be to interfere with mitogenic signals. Indeed, previous data from this laboratory suggest that one action of NGF on PC12 cells is the long term down-regulation of mitogen receptors (9,10). The present experiments demonstrate that NGF also has profound and immediate effects on mitogen signaling.…”
supporting
confidence: 57%
“…For comparison, the effects of NGF on A 2A AR expression were studied in clonal cell line 106. Clone 106, derived from PC12nnr5 cells stably transfected with TrkA, has levels of 125 I-NGF binding similar to those in native PC12 cells and differentiates in response to NGF (32). When cultures of clone 106 were treated with NGF for 1 or 3 d, both A 2A AR mRNA and protein levels were down-regulated to the same extent as native PC12 cells (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…We have previously shown that down-regulation of EGFR in PC12 cells caused by NGF treatment is dependent on p140 trk , Ras, and Src pathways (5). It is quite reasonable to ask whether these pathways are involved in the down-regulation of WT1.…”
Section: Ngf-induced Down-regulation Of Wt1 Is P140mentioning
confidence: 99%
“…Previous studies have demonstrated that NGF-induced down-regulation of the EGFR was at the transcriptional level (4) and that the down-regulation is p140 trk -, Ras-, and Src-dependent (5). Recently, we isolated and characterized the rat EGFR promoter region and found that TCC repeat sequences in the promoter region of the rat EGFR are required for the down-regulation of rat EGFR by NGF during the differentiation of PC12 cells (6).…”
mentioning
confidence: 99%